Efeitos da fotobiomodulação e do exercício de carga constante na sensibilidade barorreflexa, variabilidade da frequência cardíaca e pressão arterial no diabetes mellitus tipo 2 - Milan-Mattos, Juliana Cristina (2019)
Study 1 Aim: to evaluate cardiovascular autonomic control through time and frequency techniques in a moderate-intensity constant-load exercise session in healthy and diabetic men. Methods: We evaluated 39 men (40-64 years) divided into 2 groups: GDM2 (n=20, DM2 diagnosis) and GC (n=19, without DM2 diagnosis). The participants performed a 10 min of rest (REST), then the volunteer was positioned on a cycloergometer to start the constant workload test (1 min rest, 3 min warm-up, 6 min exercise at constant workload - EXERCISE, 6 min of cool down, 1 min of rest) followed by a 10 min of rest (RECOVERY). The workload exercise corresponded to 80% of the VO2GET (gas exchange threshold) identified by a previous cardiopulmonary exercise test (CPET). The electrocardiogram R-R intervals (BioAmp FE132) and the peripheral pulse pressure (Finometer PRO) signals were continuously collected throughout the protocol. Stable sequences of 256 points were selected for REST, EXERCISE and RECOVERY. Time domain analysis for the heart rate (HR), diastolic arterial pressure (DAP), systolic arterial pressure (SAP) variability (µ: mean and σ2: variance) and BRS (sequence method), as well as the frequency domain analysis for the HR, DAP, SAP variability (spectral analysis) and BRS (cross spectral analysis) were performed. Results: GDM2 presented lower values of μRRi and higher values of HR, higher value of low frequency in normalized units (LFnu – iRR) and more negative phase (LF) in RECOVERY compared to REST. Conclusion: GDM2 presented cardiovascular autonomic control impairment in RECOVERY, evaluated by HRV and BRS. Study 2: Aim: evaluate the effect of photobiomodulation (PBM) on cardiovascular autonomic control, analyzed by baroreflex sensitivity (BRS) (sequence method) during constant workload exercise and recovery in diabetic men. Methods: Eleven men with DM2 (40-64 years) were evaluated. The constant workload exercise protocol was performed on two different days, with a 14 days interval, to guarantee the PBM washout period. Participants were submitted to PBM (150J/300J/placebo) by light emitting diodes (LEDs), followed by the exercise protocol and equipment described in study 1. PBM was applied to the quadriceps femoral and triceps surae. Stable sequences of 256 points were selected for REST, EXERCISE, and RECOVERY. The BRS was calculated in time domain according to the sequence method (αseq). The comparison between the energies (150J/300J/placebo) and the condition (REST, EXERCISE and RECOVERY) was performed by the Two-Way Anova repeated measures test. Results: There was no interaction between energies and conditions. There was only the effect of the condition (p <0.001), showing that the behavior of αseq was similar regardless of energy. Conclusion: the PBM, previously applied to constant workload exercise test with moderate intensity in DM2, was not able to promote changes in the cardiovascular autonomic control, leading to an improvement of BRS.